2023
DOI: 10.1126/sciadv.adh0549
|View full text |Cite
|
Sign up to set email alerts
|

Earliest systematic coal exploitation for fuel extended to ~3600 B.P.

Abstract: Coal has long fueled human civilizations. The history of systematic coal fuel exploitation has been traced back to the late third millennium before present (post-2500 B.P.). Although sporadic combustion of coal for fuel was reported in some prehistoric archaeological sites, evidence for the systematic exploitation of coal for fuel before 2500 B.P. remains lacking. Here, we report comprehensive understanding for the earliest systematic exploitation of coal for fuel at the Jirentaigoukou site in Xinjiang, northw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Bayesian chronological modeling has been widely applied to restrict the age boundaries of clusters of radiocarbon dates in the research of archaeological chronology [53,[60][61][62][63]. The methods of this study were based on previous protocols, and the radiocarbon dates that were distinct from the rest of the data group were judged as outliers and were eliminated before modeling [60][61][62].…”
Section: Bayesian Chronological Modelingmentioning
confidence: 99%
“…Bayesian chronological modeling has been widely applied to restrict the age boundaries of clusters of radiocarbon dates in the research of archaeological chronology [53,[60][61][62][63]. The methods of this study were based on previous protocols, and the radiocarbon dates that were distinct from the rest of the data group were judged as outliers and were eliminated before modeling [60][61][62].…”
Section: Bayesian Chronological Modelingmentioning
confidence: 99%
“…Recent archaeological studies indicated that northern Xinjiang of northwest China acted as key passageways for the dispersal of modern humans during the late Paleolithic (Li et al, 2020) and trans-Eurasian exchange during the late Neolithic and Bronze Age (Zhou et al, 2020;Qiu et al, 2023). Liu et al explore the environmental background for prehistoric human occupations in the area based on the application of optically stimulated luminescence dating and analysis of pollen and multiple paleoclimate proxies from a loess-paleosol sequence in the Ili Valley of northwest Xinjiang.…”
Section: Editorial On the Research Topic Human-environmental Interact...mentioning
confidence: 99%
“…Generally, the Holocene has been characterized by a relatively warm and humid period, which is referred to as the Holocene Climate Optimum (HCO). During this period, the humidity/precipitation increased, and the climate was relatively stable, thus providing the basis for the rise and development of ancient cultures and civilizations [18][19][20][21]. Therefore, clarifying the onset and potential spatial differences in the HCO is essential for understanding the role of climate in the succession of human cultures and civilizations.…”
Section: Introductionmentioning
confidence: 99%